THE PECULIARITIES OF FUNCTIONAL ACTIVITY OF PHAGOCYTTING CELLS IN CHILDREN WITH SUGAR TYPE I DIABETE - E. G. Vedeshina; D. A. Domenyuk; N. Y. Kostyukova; L. G. Ivchenko; V. O. Torokhova (Современная наука и инновации, 2022)
The article presents the results of a study of the functional activity of Neutrophil granulocytes of blood in children with diabetes mellitus of 1-st type using luminol-dependent chemiluminescence. It is revealed that violations of metabolic mechanisms in children with varying severity of autoimmune diabetes is determined by the intensity of «respiratory explosion» of Neutrophilic granulocytes in lipid peroxidation system - antioxidant protection.